2019
DOI: 10.1016/j.chemgeo.2018.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Mass balance implies Holocene development of a low-relief karst patterned landscape

Abstract: We constructed mass balances of both calcium and phosphorus for two watersheds in Big Cypress National Preserve in southwest Florida (USA) to evaluate the time scales over which its striking landscape pattern developed. This low-relief carbonate landscape is dotted with evenly spaced, evenly sized, shallow surface depressions that annually fill with surface water and thus support wetland ecosystems (e.g. cypress domes) embedded in a pine-dominated upland matrix with exposed bedrock. Local and landscape scale f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 57 publications
(94 reference statements)
4
25
0
Order By: Relevance
“…Our results indicate this approach is more reliable for age dating compared with using other dating materials because of the myriad confounding factors that can impact shallow sediments in this warm carbonate‐dominated environment. Our LCFAs age dates from wetlands in BICY indicate development of the modern patterned landscape in the middle to late Holocene, in agreement with estimates from mass balance modeling (Chamberlin et al, ). During early development, RP sites were likely dominated by woody plants (e.g., cypress trees), while TR sites exhibited a dominance of graminoids, a contrast that likely arose from differences in elevation and hydroperiods.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our results indicate this approach is more reliable for age dating compared with using other dating materials because of the myriad confounding factors that can impact shallow sediments in this warm carbonate‐dominated environment. Our LCFAs age dates from wetlands in BICY indicate development of the modern patterned landscape in the middle to late Holocene, in agreement with estimates from mass balance modeling (Chamberlin et al, ). During early development, RP sites were likely dominated by woody plants (e.g., cypress trees), while TR sites exhibited a dominance of graminoids, a contrast that likely arose from differences in elevation and hydroperiods.…”
Section: Discussionsupporting
confidence: 89%
“…BP (Table ). Similar mid‐Holocene ages for initiation of the formation of depressions were found based on calcium and phosphorus mass balance estimates in BICY (Chamberlin et al, ) and theoretical estimates of the time necessary to dissolve bedrock under wetlands to a depth of 2 m (Dong et al, ). McDowell et al () reported that peats were deposited right above the limestone in the northern Everglades at ~4,280 BP.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The rapid decline in probabilities of larger basins suggests that larger, more established basins have ceased to expand laterally. Given the recent origins of the landscape pattern (Chamberlin et al, ) and the long time scales necessary for carbonate dissolution (Dong et al, ), this interpretation is tenable and leads to the prediction that dissolution rates, and thus lateral expansion, are variable with wetland size.…”
Section: Discussionmentioning
confidence: 99%